PENGEMBANGAN OBJEK WISATA DANAU KEMBAR DI KABUPATEN SOLOK (JURNAL SPASIAL, 2016)
This study aims to describe the development of tourism object in Solok District, espescially in terms of of cleanliness, safety, the arrangement of which less attention, as well as facilities and infrastructure are still lacking, so that yet provide maximum results. Type of this research is qualitative, data sources used are the words and actions that come from people who know the problems of research. The subject of this research is Department of Tourism, Subdistract, Tourism Manager, Public, and the Visitors of this tourism object. The research subject collecting by purposive sampling technique. Data collection technique done by the interviews, observation and picture taking. Data analysis techniques are reduction data, data display and interpretation of data. Data validity testing techniques in use extension of participation, perseverance, observation. Results of the study explained that : 1) The condition of the existing infrastructure and  facilities in this tourism object is still not complete. 2) The barriers development of this tourism object is visible from the road condition are not maintained, The security, the orderliness and the cleanliness arestall low. 3) in an effort to develop tourism object, it need an corporation from all related side like department of tourism, Subdistract, the manager and the society to help each other in keep the road is clean, keep it the safe, and fix the facilities and infrastructure.Keywords: Development Of Tourism, Danau Kembar, Infrastructure